Effectiveness Of 2% Isobaric In Producing Spinal Anaesthesia In Comparison to 5% Heavy Xylocaine: Effectiveness Of 2% Isobaric In Producing Spinal Anaesthesia - Prajapati, Dr Hemal; Pander, Dr Kashmira; Chavda, Dr Akash; Upadhya, Dr M R (National Journal of Integrated Research in Medicine, 2020)
Background: The objective of the study was to compare the effect of isobaric 2% Xylocaine with hyperbaric 5% Xylocaine in subarachnoid block in lower abdominal and lower limb surgeries. Method: This study was carried out in the department of Anesthesiology, Government Medical College and S.S.G. Hospital, Baroda during the period of 2004 to 2006. The study consisted of 60 patients of either sex of ASA grade I and II between age group 20 to 60 years, undergoing planned lower abdominal and lower limb surgeries. They were randomly assigned into the following two groups: Group X2 (n=30) - Patients receiving Inj. Xylocaine 2% Isobaric 4 ml (80 mg) intrathecally and Group X5 (n=30) - Patients receiving Inj. Xylocaine 5% hyperbaric 1.6 ml (80 mg) intrathecally. They were monitored for sensory block, motor block, vital parameters like pulse rate, blood pressure, oxygen saturation, duration of effective analgesia and peri-operative complications. Results were compared among the groups using unpaired "t" test and difference was considered significant when p value was less than 0.05. Result: There was no difference in mean age and weight of patients in both groups. The time for onset of sensory block, time to achieve peak sensory level, and time for sensory regression to LI level was not found to be statistically significant in both groups. The time for onset time of motor block, maximum Bromage score achieved, mean time to achieve this and the recovery of motor block to grade 0 was also similar in both groups. There was no significant change in mean pulse rate, mean systolic blood pressure, mean diastolic blood pressure and mean oxygen saturation in either of the groups at any point of study. The mean duration of surgery and duration of effective analgesia was also similar in both groups. No significant complications were found other than nausea in either of the group intra and post operatively. Conclusion: 2% isobaric Xylocaine can be very well used as an alternative to 5% hyperbaric Xylocaine in spinal anaesthesia for lower abdominal (infra-umbilical) surgeries lasting for less than one hour. [Prajapati H Natl J Integr Res Med, 2019; 10(6):27-32]